Chronic Hyperglycemia Assessed by HbA1c and Hematocrit Values in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study at a Tertiary Laboratory in Makassar, Indonesia - Amirah; Hana Yurlin; Arlitha Deka Yana Akbar; Desyani Ariza; Kasmuddin (HM Publisher, 2026)
Type 2 Diabetes Mellitus (T2DM) is characterized by persistent hyperglycemia that may impair erythrocyte function, elevate oxidative stress, and provoke osmotic diuresis, all of which could theoretically alter the hematocrit; because glycated hemoglobin (HbA1c) and hematocrit are among the most frequently requested tests in diabetes care, clarifying their relationship has direct laboratory-medicine relevance, yet reported associations remain inconsistent. This analytical cross-sectional study aimed to determine the relationship between chronic hyperglycemia, quantified by HbA1c, and hematocrit in patients with T2DM at the Clinical Laboratory of Stella Maris Hospital, Makassar, Indonesia. Forty-four outpatients with T2DM meeting predefined criteria were enrolled consecutively by purposive sampling from 27 February to 4 March 2025, and same-day HbA1c and hematocrit were analyzed. The association was assessed by Spearman rank correlation with a bootstrap 95% confidence interval (CI), at p<0.05. The mean age was 62.98 ± 11.14 years and 23 participants (52.3%) were female; mean diabetes duration was 8.80 ± 2.99 years, mean HbA1c 7.77 ± 2.52% (61.4 mmol/mol), and mean hematocrit 38.47 ± 5.45%, with only 20 patients (45.5%) reaching the HbA1c target of <7%. Spearman analysis showed no significant correlation between HbA1c and hematocrit (ρ = −0.001; 95% CI −0.30 to 0.30; p = 0.996), a negligible effect size. In conclusion, among Indonesian patients with T2DM, HbA1c was not significantly correlated with hematocrit; the hematocrit should not be used as a surrogate for long-term glycemic control, while HbA1c remains the reference standard and the hematocrit retains independent value within the complete blood count.